Strategi Pemberdayaan Komunitas Melalui Program CSR di Gampong Balee Kecamatan Meurebo Kabupaten Aceh Barat - Putri, Reihan Ayu Sukma; Darmayani, Sherlia; Azzam, Al Ismul; Maulana, Alfat; Sopar (Sagita Academia Journal, 2025)
Implementing Corporate Social Responsibility (CSR) has become an important focus for companies in their community empowerment efforts. This article analyzes community empowerment strategies through CSR programs in Gampong Balee, West Aceh Regency. The research method used is qualitative with a descriptive approach. The research results show that CSR contributes significantly to improving the social and economic welfare of local communities. Programs such as Gampong-Owned Enterprises (BUMG), catering businesses, and animal husbandry, have had a positive impact, although some initiatives require further monitoring and education. These findings emphasize the importance of collaboration between companies, government and communities in designing and implementing sustainable CSR programs, in order to achieve optimal results in community empowerment.